2 - Eurocentrism and the Contemporary Social Sciences - Keita, Lansana (Africa Development, 2020)
The contemporary social sciences emerged in the West from the eighteenth century as new modes of technology and scientific research developed. There is no doubt that technological advances led to the triumph of empiricism over metaphysics. This was the basis for the transformation of the nomenclatures of natural philosophy and moral philosophy into natural science and moral science respectively. As the empiricist methodologies of the natural sciences became successful, the social sciences chose to emulate their techniques. Thus, the methodological claim was made that that the social sciences and their division of labour compartmentalisation of the social world reflected that world in objectivist terms. But the fact that humans themselves were involved in describing and explaining the behaviours of other humans meant that a subjective element would be always be involved unless serious attempts were made for cognitive correctives and a self-conscious regard for consistent objectivity. While research in archaeology is relatively objective in its scientific findings, this is not the case with the other social sciences – especially anthropology and history. There has been an arbitrary Eurocentric creation and reification of theories and terms founded on whimsical and unsupported claims concerning the evolutionary status of Homo sapiens Africanus.